Customer loyalty in GCP - Sousa, Pedro Miguel Quintela Alves de (2015)
GCP had an annual churn rate of 33,85% in 2013. In the first 10 and a half months of 2014, the club already accounted for a 25% increase in absolute number of cancellations. The dissertation main purpose is to provide useful and practical solutions to fight this tendency. As we will determine below, customer satisfaction seems to be key to maintain or increase retention, so, understanding what is making customers unsatisfied is critical. We have conducted an internal analysis through the club’s internal data and a survey. With the survey and regular meetings with the marketing director, we tried to measure the overall level of satisfaction, as well as, the main problems related with the dropout rate from the club. One of the major reasons why customers switch service providers is because they are unsatisfied with the service and believe competitor’s value is higher. To evaluate the latter, we have also conducted an external analysis to the direct competition of GCP. The challenge proposed to this project was to define a set of strategies, aligned with the philosophy and culture of the club, to mitigate the churn rate problem. We have also proposed an implementation plan to serve as a roadmap to increase the number of members that remain at the club.